Unfastening fashion : a research experiment with a sustainable locally run workshop in Reykjavik - Cribben, Fiona Mary, 1978- (2015)
A considerable amount of resources is depleted by the textile and apparel industries every year in order to process raw fiber into a finished product. These resources include labour, energy and water. Supporting fashion trends and global-based production comes with complicated sustainability issues such as poor working conditions, cheap labour, low-quality fabrics, poor workmanship, excessive consumption and a lot of unnecessary waste. To combat these issues, a total shift is needed in the values and ideas of fashion, style and clothing design so we can ensure that sustainability becomes a standard paradigm. As designers, we can affect this change by controlling how clothing can be redesigned, so that it may in turn influence the consumer, inspire economic and social change in Iceland and afar. Half and Half is an exploratory project that shows the importance of sustainable thinking, practice and reflective action in fashion design, through recycling and the usage of natural raw materials from Iceland. This project aims to foster social quality through crafted products, the value of creating relationships and reducing waste, in the hope of bringing people into a more authentic view of fashion. A fashion that is meaningful, a fashion that engages people and connects us to each other, ourselves and our world. This research aims to inform consumers that there are other possibilities for expressing style, value and creativity in our clothing than by simply buying the latest disposable garment.